(untitled) - MUJI PRECISELY, FIBRI (RETAIN : Journal of Research in English Language Teaching, 2014)
THE USE OF AUTHENTIC LITERATURE IN TEACHING SPEAKING SKILL FOR ELEVENTH GRADERS OF SMA NEGERI 2 SRAGEN FIBRI MUJI PRECISELY English Education, Language and Art Faculty, State University of Surabaya fibrimuji@yahoo.com RIRIN PUSPARINI, S.Pd.,M.Pd Lecturer of English Study Program FBS Surabaya State University rrn.puspa@gmail.com Abstrak Menanggapi fakta bahwa ketrampilan berbicara/ speaking masih sulit untuk dikuasai oleh siswa, hal ini menuntut guru untuk mengembangkan materi mengajar mereka dalam rangka untuk membantu mereka dalam mencapai tujuan pengajaran keterampilan berbicara/ speaking. Dalam penelitian ini, peneliti menggunakan authentic literature sebagai bahan pendukung untuk mengajar berbicara . Authentic literature yang diterapkan dalam penelitian ini adalah teks narasi dalam bentuk cerita pendek. Kemudian penggunaan Authentic lIterature yang diterapkan oleh siswa adalah dengan mempersembahkan presentasi dan drama. Penelitian ini dilakukan di SMA Negeri 2 Sragen . Subyek dari penelitian ini adalah siswa kelas XI program sains . Deskriptif kualitatif dilakukan sebagai desain dari penelitian ini. Dalam penelitian ini, peneliti mengumpulkan data dari pengumpulan bukti tertulis , kuesioner dan wawancara. Pengumpulkan bukti tertulis digunakan karena peneliti ingin mengetahui dari pnerepan authentic literature dalam mengajar ketrampilan berbicara berbicara/ speaking. Kemudian, kuesioner dan wawancara digunakan karena peneliti ingin mengetahui respon siswa terhadap penggunaan authentic literature dalam mengajar ketrampilan berbicara/ speaking. Data yang diperoleh selama penerapan authentic literature dalam mengajar keterampilan berbicara adalah dengan melakukan dua aktifitas, yaitu presentasi dan drama. Dengan demikian, dapat disimpulkan bahwa authentic literature dapat digunakan sebagai materi pendukung yang sesuai untuk mengajarkan ketrampilan berbicara/ speaking. Peneliti menyarankan para guru untuk lebih kreatif dalam memberikan dan menerapkan materi lain yang dapat mendukung untuk mengajarkan ketrampilan berbicara/ speaking. Untuk peneliti lain, penelitian ini masih jauh dari sempurna. Oleh karena itu, diharapkan ada diskusi yang sama dengan penelitian ini dan akan memberikan kontribusi dalam mengajarkan ketrampilan berbicara/ speaking sebagai materi pendukung. Kata Kunci: speaking skill, authentic literature Abstract Responding to the fact that speaking is still difficult to be mastered by students, it demands teachers to develop their teaching material in order to help them to achieve the goal of teaching speaking skill. In this study, the researcher used authentic literature as a supported material to teach speaking. The authentic literature which was implemented in this research was a narrative text in the form of short story. Then the implementation of the authentic literature would be practicing students’ speaking skill by performing presentation and role play. This research was conducted in SMA Negeri 2 Sragen. The subject was the eleventh graders of science program. Descriptive qualitative was conducted as the design of this research. In this researcher, the researcher collected the data from gathering documentary evidence, questionnaire and conducting interviews. Gathering documentary evidence was used since the researcher wanted to know the implementation of authentic literature in teaching speaking. Then, questionnaire and interview was conducted since the researcher wanted to know the students’ response toward the using of authentic literature in teaching speaking. The data obtained during the implementation of authentic literature in teaching speaking skill was by making performances, those are presentation and role play. As result, it can be concluded that authentic literature could be used as an appropiate supported material in teaching speaking skill. The researcher suggests the teacher to be more creative in giving and applying the other material to teach speaking. For other researchers, this study is far from perfect. Other research in the same discussion will give contribution to the teaching of speaking that can be used as a supported material. Keywords: speaking skill, authentic literature introduction Speaking is one of tools for human to communicate each other in language they have agreed in order to receive, produce, and process information. According to Brown (1994) and Burns & Joyce (1997), speaking is “an interactive process of constructing meaning that involves producing and receiving and processing information”. Moreover, speaking considered as process: “speaking is also process of building and sharing meaning through the use of verbal or non-verbal symbols in a variety of contexts”, Chaney (1998). Ur (1996) says that “of all the four skills (listening, speaking, reading, writing), speaking seems intuitively the most important”. Bygate (1987) analyzes that being a good learner of speaking, students must learn knowledge of grammar, vocabulary, pronunciation, intonation, and etc in order to communicate fluently. Unfortunately, in real situation students who still in school period whether Junior or Senior High School cannot speak in English well. According to Brown (2001) there are four problems in speaking skill those are: (1) Inhibition. Since speaking is being very important to acquire however, in real situation they warned about making mistakes, fearful of criticism, and simply shy in getting attention of their speech. (2) Have nothing to say occurs when there’s no motivation in expressing the idea and also boredom in speaking then as consequences they can’t bring their ideas out. (3) Low or uneven participation is when learners do not have much time to practice the speaking because the condition in class itself is teacher centred, and overcrowded classroom. Otherwise, there will be dominated learner while other speaks very little or not at all. (4) Mother tongue use happens because Indonesia has its own mother tongue, they are the vernaculars or Bahasa then it makes English considered as the foreign language and it does not use daily in society. Facing those problems, teacher must do some treatments in order to build students’ speaking skill, so that the number of reluctant students can be decreased. Teacher must improve their teaching and adjust it to students’ desire. One of ways in doing so is by developing the teaching materials. (Mulyasa, 2007, p.204) says that based on KTSP, there are some matters that should be taken into consideration in identifying the standards materials, namely: a. The development level of the laearners physical, intellectual, emotional, social, and spiritual b. The usefulness for the learners c. The scientific structure d. The depth and the windth of the materials e. The relevance with the learners need and the society demand. Responding to those considerations, the use of authentic literature seems to be appropriate for the developing material in teaching speaking for eleventh graders of Senior High School. According to Ha (2002) as cited in Phat (2013) entitled The Implementation of Literature in Teaching Speaking for Advance Students notes down that literature is not always a fiction; in fact, it is the production of certain reality. If “imaginative” is exclusively attributed to literature, does it imply that other kinds of writing such as philosophy, history or unimaginative? So fiction and realism are not the concepts for the production of literature. Although the implementation of authentic literature is through reading however according to Day and Bamford (1998) as cited in Thomas (2006) entitled Developing Presentation Skill by Using Authentic Litrature, he reviews several studies of extensive reading programs; these studies indicates that students who read extensively not only improve their reading proficiency and writing skills, but also their vocabulary, and even their listening and speaking skill. So that it can be seen that it is appropriate to use authentic literature in teaching speaking skill. Supported by Phat (2013) says that studying literature can foster the students’ interpretations and enhance their language and communication skill. Taken from the journal belongs to Patki (2013) entitled “Development of Speaking Skills through Authentic Literature” states that there are three appropiate materials in teaching speaking by using authentic literature, those are: a. Prose Written on this journal that stories is very effective in teaching speaking as it is very interactive. It is so since stories enrich students’ visual imagination and creativity. It organizes, retains, and assists students to acces information. So that, it brings out the emotions which provokes learning. Moreover, once the initial hitch of speaking is removed, the students become more confidence in delivering their thoughts. Furthermore, when they see their story are got attention, valued, recognized, and heard with interest, it gives them confident to stand. Thus, it can be seen by using stories can develop students’ positive attitude towards the learning process. In addituion, stories bring many advantages for students in learning speaking skill since it can improve students’ vocabulary, sentences formation, the use of tense and verb but also work positively on students’ fluency when they speak. So that, it can be concluded that stories assist students to build up an overall personality of students as they are connected to the society directly, improving their communication. b. Poetry Based on this journal says that poetry is such a sophisticated literacy tool that it works on the moods and emotions of the students. Through poetry the students are able to express and deliver their point of view without concerning on grammatical accuracy. Through poetry the students are facilitated with awareness of pronunciation, intonation, sentences flow. Moreover, they also practice their specific language structures such as phrases, idioms, work order, and verb tense. Moreover, when teacher gives poetry for students and ask them to analyze it automatically it creates an atmosphere for students to get involve in discussion. Hence, they will talk about their responses, ideas and etc. So that, it absolutely enrich their confidence in speaking fluently. c. Drama Basically, through drama, it offers ways for students to have chances to respond to and express their individual thought and shared understanding of a text. Because evetually, when students work in drama/ role play, they got the opportunity to use the languase as it is used in real life and gain confidence as when they act and assume roles and interact improvisation. Hence, when the students want to acquire the proficient speaking skill, drama has always been great help for it. It is so since when they play drama they also play a certain roles which might be familiar for them, so that it brings out their inner potential to think deeply and express their ideas. They are also able to express themselves explicitily as they can relate to the characters they play. Unconsiously, they are working on their imaginations, vocabulary, structure sentence, stress, intonation, and rhythm. Moreover, the modulation of tone is important during the dramatization so that when students work on it, it automatically enhances their speaking skill. In this research, the authentic literature that implemented in building students’ speaking skill was a short story which is narrative text. Collon and Villa (1997) comment that storytelling helps EFL learners become more self-confident to express themselves spontaneously and creatively. However, the implementation of authentic literature for speaking skill is suitable based on curriculum 2006 KTSP for second semester of Eleventh Grade of Senior High School in Standar Kompetensi (berbicara/ speaking) “Mengungkapkan makna dalam teks fungsional pendek dan esei berbentuk narrative, spoof, dan hortatory exposition dalam konteks sehari-hari”. In implementing the authentic literature, the teacher used three phases speaking activity, those are: Pre Activity In pre-activity, the teacher tells the objective of the study that they are going to learn. They will practice speaking by having performances through authentic literature. Then, the teacher informs the title of the authentic literature which they are going to use. Whilst Activity In whilst activity, there are pre-speaking, whilst speaking and post speaking. First, in pre-speaking, the teacher gives the authentic literature in form of narrative text that is short story. Then, the teacher asks the students to read the story carefully and also asks the students to make a group. Each group consists of ten students. Second, in whilst speaking, they are asked to discuss the content of the story given by making an outline or draft. After they finish doing the outline or draft, the teacher asks the students to develop their outline into paragraph for the presentation and dialog for the role play. Third, in post speaking, based on the paragraph and dialog they have made, the students are asked to make performances, those are presentation for the second meeting and role play for the third meeting. However for the first meeting the students are only asked to discuss the first text given and deliver it orally by raising hand. Post Activity In post activity, the students submit their paragraph of presentation and dialog of role play to the teacher. Then, the teacher gives the additional explanation and asks the students’ difficulties in doing their speaking. This study outlines two objective, those are “To describe the implementation of using authentic literature in teaching speaking skill for eleventh graders in SMA Negeri 2 Sragen” and “To decribe the students’ response toward the implementation of authentic literature in building students’ speaking skill for eleventh graders in SMA Negeri 2 Sragen” A point to be noted is that in order to be focused on the analysis only, the writer limits the problems as follows: the study only focuses on the speaking skill which is using authentic literature in form of short story/ narrative text as a supported material to enhance students’ speaking ability for Second Grade of Senior High School. METHODOLOGY This is descriptive qualitative study. It involves a collection of the techniques that is used to specify, delineate, or describe naturally occurring phenomena without experimental manipulation (Selider and Shohamy, 1997, p.124). (Bogdan and Biklen, 1992, p.29) state that there are three characteristics of the qualitative research. First, it has the natural setting as the direct source of data and the researcher is the key instrument. Second, it is descriptive since the data are collected in the form of words or pictures rather than numbers. Third, the researcher is concerned with the process rather than simply with outcomes or products. The subject of the study was eleventh graders of Senior High School (Sekolah Menengah Atas) Negeri 2 Sragen. The researcher took the students only since there was no scoring which might be done by the teacher. On the other hand, she chose this school since the material that will be treated which is Authentic Literature is applied in class. The data of the study will be students’ performances towards the use of authentic literature in speaking class. In doing so, the writer observed the class activity from the beginning until the end of the lesson. The writer would act as non-participant observer that is paying attention to the students’ learning process, gathering data from students’ performance, those were paragraph from the presentation and dialog from the role play. Gathering data evidence from presentation and role play were used to figure out the first objective. Then the questionnaire and interview were used to answer the second objective. RESULT AND DISCUSSION The Implementation of Authentic Literature in Teaching Speaking Skill There were three activities which had been conducted in implementing this research; pre-activity, whilst activity (pre-speaking, whilst-speaking, post speaking), and post activity. First, in pre-activity, the teacher started the class activity by explaining to the students about the objective of the study they learnt. The teacher told that they were going to use authentic literature in form of narrative text that was short story as a supported material in teaching speaking skill. In that moment, the students seemed very enthusiast and excited. According to Butt (2005: 225) states that narrative is a special kind of story that is valued very highly in English- speaking cultures. Narrative are structured to be entertaining and to teach values. Second, in whilst activity, there were three speaking activities which had done by the teacher. They were pre-speaking, whilst-speaking, and post speaking. In pre-speaking, the teacher gave the authentic literature for the students then asked them to read it carefully. Through reading the authentic literature, the students were able to learn about the grammar, vocabulary and translation. These were supported by Liaw (2001) says that literary works provides additional material of grammar practice, vocabulary learning, and translation. Although reading and speaking are not intuitively close but from the explanation above can be seen that by reading students get some aspects which support them to improve their speaking skill. In whilst-speaking, after reading the short stories the students were asked to make performances, those are presentation for the second meeting activity and role play for the third meeting activity and there was no performances in first meeting but discussion in group. Based on journal Patki (2013) there are some literary works which can be applied in teaching speaking those are poetry, prose, drama. In making performances the students were asked to work in group so that they can practice their speaking skill with their friends in discussion. So that, through literary work settings, role relationships are predetermined and social context is taken into consideration, so it can be used for increasing the awarness of the students about language use, McKay (1982). Moreover, considering that they had discussion in making the performances, it is matched with Lazar (1993) which notes down that literature can be used as tool for creating opportunities for discussion, controversy, and critical thinking. Thus, by having those activities in whilst-speaking it exactly can be said that those were very helpful for students in practicing their speaking skill since they were given material to deliver. In post-speaking, the students were asked to perform their speaking activities, those were presentation in second meeting and role play in third meeting. Third, in post activity, the teacher gave feedback towards students’ performances and asked them to submit their paragraph of presentation and script or dialog of role play or drama. The Students’ Response Toward The Use of Authentic Literature in Teaching Speaking Skill The writer used questionnaire and conducting interviews since she wanted to know the students’ responses toward the using of authentic literature in teaching speaking. Taken from the questionnaire and interview showed that most of them were interested in applying the authentic literature. It is so since the narrative texts given were entertaining so that it made them to be more willing in attending the teaching and learning process which was speaking skill. Derewianka (1990: 40) a narrative text is a text which has a purpose to entertain, i.e. to gain and hold the reader’s interest in a story, to teach or inform, to embody the writer’s reflections on experience, and perhaps most important – to nourish and extend the reader’s imagination. They also assumed that authentic literature ease them in learning speaking skill. It is so since through authentic literature they can learn some aspects which supported in making speaking. Those are understanding the phrases, idioms, vocabulary, various parts of speech. Cited on journal named Patki (2013) explains that through the different tools of literature, the students comprehend and learn the lexical item, semantics, vocabulary, phrases, idioms, use of tenses and various parts of speech which, undoubtedly, enhance their speaking skill. CONCLUSION AND SUGGESTION Conclusion Based on the result of the data analysis which is obtained through observation, questionnaire and conducting interviews, the researcher concludes that: 1. Authentic Literature is very acceptable in teaching speaking skill. It is so since authentic literature is able to increase students’ interest to speak up in English. Authentic literature provides interesting activity, those are presentation and role play. By doing those activities it awares the students toward the language use which is necessary in practicing the speaking skill. Moreover, by reading the authentic literature can help the students in enhancing some aspects, those are translating, understanding the vocabulary, grammar practice which those things are necessary in speaking. 2. The students’ response toward the use of authentic literature in teaching speaking was good. Based on the questionnaire and conducting the interview proved that the students’ enjoyed and excited in attending the teaching and learning process which was speaking activity. It happened since by using the authentic literature, teacher could create a good competitive condition which all students were actively participated in class activities. The target language functions could be understood by and used by the students’ appropriately. Suggestion Based on the result of the data analysis and the conclusion above, the researcher suggests that Authentic Literature is appropiate to be applied in teaching speaking skill. Although the Authentic Literature selected by the researcher was narrative however there are many other Authentic Literature that can be applied in teaching English, especially for speaking skill. Thus, in order to ease the teacher in delivering the material the teacher must know students’ interest, so that they can take part in teaching and learning process actively. As a result, the students are able to communicate in English fluently and accurately. REFFERENCES Bogdan, R. C. and Biklen, S. K. (1992). Qualitative Research for Education. Boston: Advison of Sinn and Schuster, Inc. Brown, James Dean. (2001). Using Surveys in Language Programs. UK: Cambridge University Press. Butt, David, et. Al. (2000). Using Functional Grammar. 2nd ed. Sydne: Macquire. Colon-villa, L. (1997). Storytelling in the ESL Classroom. Teaching K-8, 58-59. Day, R. R., & Bamford, J. (1998). Extensive reading in the second language classroom. Cambridge: Cambridge UP. Derewianka, Beverly. (1990). Exporing How Tes Work. Rozelle: Primary English. Ha, V. L. (2002). Literature in the EFL Language-Teaching Class. Research Exercises-A Collection, 1, 101-115. Lazar, G. (1993). Literature and language teaching: a guide for teachers and trainers. Cambridge: Cambridge University Press. Liaw, M.-L. (2001), Exploring Literary Responses in an EFL Classroom. Foreign Language Annals, 34, 35–44. Badan Standar Nasional Pendidikan. (2006). Standar Kompetensi dan Kompetensi Dasar Bahasa Inggris. Jakarta. Badan Standar Nasional Pendidikan (BNS) Mc Kay, S. (1982). Literature in ESL Classroom. TESOL Quarterly, 16 (4), 529-536. Mulyasa, E. (2006). Kurikulum Tingkat Satuan Pendidikan. Bandung: Remaja Rosdakarya. Phat, C.H. (2013). The Implementation of Literature in Teaching Speaking for Advance Students. Vol.1, No 2. Viet Nam. Ho Chi Minh University of Education. Thomas, H. K. Developing Presentation Skill by Using Authentic Literature. The Internet TESL Journal, Vol. XII, No. 11, November (2006). New York. Kingsborough Community College. Selider, H. W. and Shohamy, E. (1997). Second Language Research Methods. New York: Oxford University Press.